What affected the vitality of high-speed rail station areas? A case study of Chengdu-Chongqing urban agglomeration, China - Yang, Xian; Yu, Yang; Peng, Panyu; Liu, Chong (Frontiers in Environmental Science, 2024)
With the rapid expansion of high-speed rail (HSR), the HSR station areas are often the key development areas of the cities and the gateways to display the cities' image. However, the problem of lack of vitality in these areas has emerged. Limited studies have quantified the vitality of HSR station areas and examined the factors influencing it. The purpose of this study is to assess the impact of various factors on the vitality of HSR station areas. To accomplish this objective, we propose a method for measuring the vitality of HSR station areas using Baidu's real-time user density data. We demonstrate the method through the case study of 91 HSR station areas in the Chengdu-Chongqing urban agglomeration in China. We construct structural equation models using a Bayesian approach to test the effects of intercity accessibility, intracity accessibility, surrounding area density, and local socio-economic development on the vitality of HSR station areas. The results show that (1) Intracity accessibility, surrounding area density, and local socioeconomic development have significant positive effects on the vitality density of HSR station areas. Intercity accessibility has a negative effect on the vitality density of HSR station areas. (2) Surrounding area density positively influences the stability of weekday and weekend vitality in HSR station areas. Local socio-economic development negatively impacts the stability of weekend vitality in HSR station areas. (3) High-vitality HSR station areas are mostly located in Chengdu and Chongqing, both megacities. Station areas with low vitality are primarily located in small cities. This study's findings can be used to guide the planning and decisionmaking of HSR station areas aimed at enhancing their vitality.